Magneto-Thermoelastic Analysis of Ferromagnetic Plate Exposed to High-Frequency Induction Heater - Balpande, B. B.; Kedar, G. D. (Communications in Mathematics and Applications, 2025)
A mathematical model for studying the consequences of a moving high-frequency induction heater on a ferromagnetic plate material was presented in the context of Maxwell’s equation. Conducting currents are generated when the material is exposed to electromagnetic fields operating at high frequency. The losses due to conducting currents and the hysteresis effect are summed and considered as the total heat loss of the problem. The expressions for heat losses, temperature field, elastic field, and magnetic field are obtained across the plate material in the context of Maxwell’s equations and Ohm’s law and are solved using the double finite Fourier sine and Marchi-Fasulo integral transforms. Lastly, the effects of the plate dimensions, frequency, and velocity of the heater and the resistivity are discussed and analyzed graphically. The result of the presented investigation will enable us to ensure the feasibility of the efficient design and construction of electric devices with magnetic circuits characterized by reduced heat losses.